Estudio de la influencia de la fertilizacion nitrogenada y la iluminacion sobre atributos morfologicos y fisiologicos de brinzales de Q.suber L. CULTIVADO EN VIVERO. RESULTADOS DEL 1er. AÑO EN CAMPO - Martínez Romero, G.; Planelles González, R.; Zazo Muncharaz, J.; Bela Quero, D.; Vivar Sanz, A.; López Arias, M. (III Congreso Forestal Español Congreso, 2001)
This essay studies the influence of fertilization and illumination of Q.suber L. in container seedlings. Plants were tested in three diferents levels of fertilization (control substrate, fertilizated substrate and fertilizated substrate plus nitrogen supplied) with two of illumination (full light conditions and a reduction of 50% illumination). After the first year in nursery, plants was installed in survey parcels, where growing measures and survival rates were studied
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: Cork oak; fertilization; ilumination; Quercus suber L.

Estudio de la influencia de la fertilizacion nitrogenada y la iluminacion sobre atributos morfologicos y fisiologicos de brinzales de Q.suber L. CULTIVADO EN VIVERO. RESULTADOS DEL 1er. AÑO EN CAMPO - Martínez Romero, G; Planelles González, R; Zazo Muncharaz, J; Bela Quero, D; Vivar Sanz, A; López Arias, M (III Congreso Forestal Español Congreso, 2001)
This essay studies the influence of fertilization and illumination of Q.suber L. in container seedlings. Plants were tested in three diferents levels of fertilization (control substrate, fertilizated substrate and fertilizated substrate plus nitrogen supplied) with two of illumination (full light conditions and a reduction of 50% illumination). After the first year in nursery, plants was installed in survey parcels, where growing measures and survival rates were studied
Keywords: Cork oak; fertilization; ilumination; Quercus suber L.